2019
DOI: 10.1152/ajpgi.00145.2019
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine against gastrin, a polyclonal antibody stimulator, decreases pancreatic cancer metastases

Abstract: Growth of pancreatic cancer is stimulated by gastrin in both a paracrine and an autocrine fashion. Traditional therapies have not significantly improved survival, and recently pancreatic cancer has been deemed a “cold” tumor due to its poor response to immunotherapy. Strategies to improve survival of pancreatic cancer are desperately needed. In the current investigation, we studied the effects of an anti-gastrin cancer vaccine, polyclonal antibody stimulator (PAS; formerly called G17DT and Gastrimmune), used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Furthermore, gastrin and its receptor, GRPR, promote EMT by increasing Snail and reducing E-cadherin expression [9]. However, polyclonal antibody stimulator (PAS), an anti-gastrin cancer vaccine, inhibits tumor formation, metastases of pancreatic cancer, and gastrin-induced EMT [48]. CXCL12-induced CXCR7 receptor results in increased IL-8 and VEGF levels, and subsequently, EMT by induction of Snail through the activation of AKT, ERK, and STAT3 in bladder cancer and BC [49,50].…”
Section: Critical Modulators Of the Jak2/stat3 Signaling Pathway In Emtmentioning
confidence: 99%
“…Furthermore, gastrin and its receptor, GRPR, promote EMT by increasing Snail and reducing E-cadherin expression [9]. However, polyclonal antibody stimulator (PAS), an anti-gastrin cancer vaccine, inhibits tumor formation, metastases of pancreatic cancer, and gastrin-induced EMT [48]. CXCL12-induced CXCR7 receptor results in increased IL-8 and VEGF levels, and subsequently, EMT by induction of Snail through the activation of AKT, ERK, and STAT3 in bladder cancer and BC [49,50].…”
Section: Critical Modulators Of the Jak2/stat3 Signaling Pathway In Emtmentioning
confidence: 99%
“…Furthermore, it consistently changed the microenvironment in several animal models (pancreatic and gastric) leading to a synergistic effect with checkpoint inhibitors ( 31 ). The prevention of metastases in mice treated with PAS ( 44 ) was due to the inhibition of epithelial mesenchymal transition, and this mechanism of action may help explain the long-term survivors previously observed in the clinical program. The decreased fibrosis observed with PAS therapy may help to explain the synergy previously found with gemcitabine.…”
Section: Discussionmentioning
confidence: 87%
“…The mT3-2D murine tumor recapitulates human PDAC in that it grows rapidly, has mutant KRAS G12D , and develops the typical dense fibrotic stroma in the TME [ 27 , 31 ]. Using this immunocompetent model, we found that therapy with the CCK receptor antagonist, proglumide, slowed the growth of pancreatic tumors by the same magnitude as gemcitabine treatment compared to PBS-treated controls ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%